Those who understand the time Graniceros front ends or the Sierra de Texcoco - Lorente Fernández, David (2017)
Based on the collective memory of a series of communities and on ritual practices carried out today in a clandestine manner, this article analyses some ritual specialists which are chosen by lightning in the Sierra de Texcoco, using ethnographic evidence and field observations done by the author.  The text describes these ritualists’ particularities in the context of the local cosmological system and contrasts them with existing «graniceros» in other areas of Mexico. The article covers four main elements: the nature of recruitment, the initiation, the specific roles of these atmospheric ritualistic and their social situation in the communities of the Sierra de Texcoco, a Nahua region close to Mexico City with a remarkable historical depth and a sense of memory that is reflected in representations and ritual practices that have been played creatively for a long time path.